Bioethics and society’s functional organization - Morandé Court, Pedro (Acta Bioethica, 2002)
Bioethics' interdisciplinary interchange, difficult and arduous, is this article's aim. First of all in relation to bioethics' fortuitous novelty and creativity from the mind's point of view. Essentially this reflection develops within philosophy's field, through a question that guides its analysis: what does bioethics add to the traditional ethical debate that has taken place in the midst of all cultures? In second place, through a sociological type of view, on the space that bioethics occupies in a multifunctional society. In this perspective, this text questions itself on the possibility of developing a bioethics concept that involves the whole society, that is, that it generates the same legitimacy and esteem in all sectors functionally differenciated.